Implementation of the Project-Based Learning (PjBL) Learning Model in Indonesian Language Learning to Improve the Ability to Write Simple Sentences in Grade II Students of MIS Sambinae, Bima City - M. Asyifa; Fuaddudin; Nurul Farhin (Lembaga Bale Literasi, 2026)
This study aims to determine the effect of implementing the Project-Based Learning (PjBL) model on second-grade students' ability to write simple sentences in Indonesian language instruction at MIS Sambinae in Bima City. This study employs a quantitative experimental approach using a pre-experimental one-group pretest–posttest design. The research subjects were all second-grade students at MIS Sambinae in Bima City, who were selected as the sample using total sampling. Data collection was conducted through tests, observations, and documentation. The research instrument consisted of a simple sentence writing test administered before (pretest) and after (posttest) the implementation of the Project-Based Learning (PjBL) model. The research results indicate that implementing the Project-Based Learning (PjBL) model positively affects students' ability to write simple sentences. This is evidenced by an improvement in student learning outcomes, where the average pretest score of 58.4 increased to 81.6 on the posttest. In addition, the minimum score increased from 40 to 65, and the maximum from 75 to 95. This improvement indicates that the Project-Based Learning (PjBL) model can enhance students' ability to construct simple sentences and to use vocabulary, capital letters, and punctuation more accurately. Although there were several challenges in its implementation, such as differences.